Rubella Virus- and Cytomegalovirus-Associated Anterior Uveitis: Clinical Findings and How They Relate to the Current Fuchs Uveitis Syndrome Classification - Yermalitski, Anton; Rübsam, Anne; Pohlmann, Dominika; Metzner, Sylvia; Pleyer, Uwe (Frontiers in Ophthalmology, 2022)
Rubella virus (RV) and cytomegalovirus (CMV) have both been implicated in anterior uveitis (AU). Clinical phenotypes can vary widely among both etiologies, including Fuchs uveitis syndrome (FUS) as a very distinct phenotype that has been associated with both RV and CMV. The Standardization of Uveitis Nomenclature (SUN) Working Group recently updated the classification criteria for FUS as unilateral AU, including either heterochromia or diffuse iris atrophy combined with stellate keratic precipitates as key findings. The aim of this study was to determine whether our patients adhere to the classification criteria of FUS as previously reported and whether RV- or CMV-associated uveitis can be differentiated by clinical findings. Therefore, this study investigated the clinical characteristics of patients with AU and intraocular presence of either RV or CMV determined by the Goldmann–Witmer coefficient (GWC). Our study included 100 patients (107 eyes) with AU and positive GWC for RV (86) and CMV (21). Clinical findings of RV-positive eyes were as follows: keratic precipitates (91.9%) with a predominantly diffuse distribution (81.4%), unilateral cataract (80.2%), pseudophakia (73.5%), and vitreous cells (59.7%), whereas heterochromia was present in only 39.5% of eyes and iris atrophy in 12.9% of eyes. In CMV-positive eyes, conversely, a higher incidence of ocular hypertension with markedly increased intraocular pressures above 30 mmHg (66.7%), keratic precipitates (81.0%), which were most commonly distributed in the center of the cornea (63.6%), an unaffected lens (55.0%), absent iris atrophy (100%), and absent posterior synechiae (90.5%) could be detected. This indicates a clinical presentation that was mainly compatible with Posner–Schlossman syndrome. In our cohort of RV-positive FUS patients, we saw a different cluster of clinical findings compared to the classification criteria suggested by the SUN Working Group. The main criteria, such as unilaterality, were mostly fulfilled. When applying all classification criteria, only 8.4% of 107 eyes and 10.5% of all 86 RV-positive eyes would qualify for the diagnosis of FUS. In addition, in our cohort of predominantly Caucasian patients, the clinical findings in patients with proven CMV infection differed from the clinical presentation typically associated with FUS.